2012
DOI: 10.1063/1.4716010
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling resistance and its effect on the electrical conductivity of carbon nanotube nanocomposites

Abstract: In this paper, we examined the effect of electron tunneling upon the electrical conductivity of carbon nanotube (CNT) polymer nanocomposites. A CNT percolating network model was developed to account for the random distribution of the CNT network using Monte Carlo simulations, where the tunneling resistance between CNTs was established based on the electron transport theory. Our work shows several novel features that result from this tunneling resistance: (i) direct contact resistance is the result of one-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
140
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(152 citation statements)
references
References 59 publications
2
140
0
1
Order By: Relevance
“…Several authors [54,[76][77][78][79][80] have reported that the electrical properties of nanocomposites are governed by electron hopping or tunnelling. Experiments and models revealed that the electron tunnelling results in nonlinear current-voltage behaviour in nanocomposites [81,82]. The resistance between nanotubes is a combination of direct contact resistance and tunnelling resistance [83].…”
Section: (C) Equivalent Resistor Networkmentioning
confidence: 99%
“…Several authors [54,[76][77][78][79][80] have reported that the electrical properties of nanocomposites are governed by electron hopping or tunnelling. Experiments and models revealed that the electron tunnelling results in nonlinear current-voltage behaviour in nanocomposites [81,82]. The resistance between nanotubes is a combination of direct contact resistance and tunnelling resistance [83].…”
Section: (C) Equivalent Resistor Networkmentioning
confidence: 99%
“…[102,103] This type of electrical transport is commonly described in the framework of the variable range hopping (VRH) model, [86,95,103] according to which the resistance of a CNT film is given by (12) where E 0 is the activation energy of electron hopping between neighboring tubes, T is the temperature, and β is given by 1/(d+1), where d is the dimensionality of the electrical transport. Accordingly, the TCR of CNT films is given by (13) Based on Eq.…”
Section: Bolometers Based On Swcnt-polymer Compositesmentioning
confidence: 99%
“…The quantum tunneling mechanism based on the percolation theory has been investigated in black carbon and carbon nanotube polymer Electronic addresses: gc@ecs.soton.ac.uk and sli@mail.xjtu.edu.cn composites. 10,11 We believe that it can also be used to represent the charge conduction in nanodielectrics loaded with metallic oxide. For high loading concentration, the separation distance between the two adjacent nanoparticles is short.…”
mentioning
confidence: 99%